Dimensions of ritual economy - Wells, E. Christian; McAnany, Patricia Ann (Research in economic anthropology ;, 2008)
Increasingly, economists have acknowledged that a major limitation to economic theory has been its failure to incorporate human values and beliefs as motivational factors. Conversely, the economic underpinnings of ritual practice are under-theorized and therefore not accessible to economists working on synthetic theories of human choice. This book addresses the problem by bringing together anthropologists with diverse backgrounds in the study of religion and economy to forge an analytical vocabulary that constitutes the building blocks of a theory of ritual economythe process of provisioning and consuming that materializes and substantiates worldview for managing meanings and shaping interpretations.The chapters in Part I explore how values and beliefs structure the dual processes of provisioning and consuming. Contributions to Part II consider how ritual and economic processes interlink to materialize and substantiate worldview. Chapters in Part III examine how people and institutions craft and assert worldview through ritual and economic action to manage meaning and shape interpretation. In Part IV, Jeremy Sabloff outlines the road ahead for developing the theory of ritual economy. By focusing on the intersection of cosmology and material transfers, the contributors push economic theory towards a more socially informed perspective.